Treatment of pigment epithelial detachments due to age-related macular degeneration with intra-ocular C3F8 injection - Gross-Jendroska, Mirjam; Flaxel, Christina J; Schwartz, Steve D; Holz, Frank G.; Fitzke, Fred W; Gabel, Veit-Peter; Bird, Alan C (Australian and New Zealand journal of ophthalmology, 1998)
Purpose: To flatten pigment epithelial detachments (PED) cue to age-related macular degeneration in an attempt to visualize the underlying choroidal neovascularization by fluorescein angiography (FA) and reveal a treatment target. Methods: Nine patients with PED received intravitreal gas injections via the pars plana and postured face down. Fluorescein angiograms were obtained before and after gas injection. In two patients, retinal scotopic sensitivity was also measured. Results: Eight patients demonstrated change in the shape and size of the PED following gas injection. Four patients showed a better delineation of underlying structures on FA. Three patients had focal laser treatment to the newly visible choroidal neovascular complex, but this was successful in only one patient with flattening of the PED. Conclusion: Pigment epithelial detachments can be modified by intravitreal gas injection in some patients, but this treatment did not have a major impact on overall outcome or management.
Elektronische Reproduktion der Druck-Ausgabe 7. Dezember 2009
Gesehen am 17.11.2025